Influence of moisture content on physical and mechanical properties of Calophyllum sp wood - Arroyo, Felipe Nascimento; Fraga, Iuri Fazolin; Ruthes, Heloiza Candeia; Soares, Larissa Soriani Zanini Ribeiro; de Moura Aquino, Vinícius Borges [UNESP]; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (Universidade Federal de Santa Maria, 2023)
Due to its excellent resistance to traction and compression, wood is regularly used in furniture, window frames and in structures and sealing of homes and buildings. Due to the anisotropy and complexity of the material, its properties vary depending on its intrinsic anatomical characteristics and external factors, such as species, moisture content, acting requests, among others. The Brazilian standard provides linear models for estimating and correcting all strength and stiffness properties as a function of the moisture content of the wood. However, due to its characteristics, there may not be a linear variation of the physical and mechanical properties in relation to the moisture content. Thus, this research aims to evaluate and analyze the influence of moisture content on 15 properties of Calophyllum sp. The reliability of the Brazilian standard equation for correcting strength and stiffness values as a function of humidity (U% to 12%) was evaluated, in addition to analyzing, through ANOVA, whether there is a change in the properties when they are at the saturation point of the fiber and 12% moisture. Of the 15 properties analyzed, 4 did not change, contrary to the linear models set out in the Brazilian standard. In addition, it was possible to note that the Brazilian standard can estimate with an error of up to 76% when correcting the humidity to 12%.
Influência do teor de umidade nas propriedades físicas e mecânicas da madeira Calophyllum sp
Keywords: Catanudo; Linear model; Moisture content